Oncolytic viruses-modulated immunogenic cell death, apoptosis and autophagy linking to virotherapy and cancer immune response - Wu, Yi-Ying; Sun, Te-Kai; Chen, Ming-Shan; Munir, Muhammad; Liu, Hung-Jen (Frontiers in Cellular and Infection Microbiology, 2023)
Recent reports have revealed that oncolytic viruses (OVs) play a significant role in cancer therapy. The infection of OVs such as oncolytic vaccinia virus (OVV), vesicular stomatitis virus (VSV), parvovirus, mammalian reovirus (MRV), human adenovirus, Newcastle disease virus (NDV), herpes simplex virus (HSV), avian reovirus (ARV), Orf virus (ORFV), inactivated Sendai virus (ISV), enterovirus, and coxsackievirus offer unique opportunities in immunotherapy through diverse and dynamic pathways. This mini-review focuses on the mechanisms of OVs-mediated virotherapy and their effects on immunogenic cell death (ICD), apoptosis, autophagy and regulation of the immune system.